Creation and implementation of a library interactive media for the documentation of the shoe making process in Marikina - Legaspi, Charlotte Coleen D.; Buenrostro-Cabbab, Iyra, S.; Obille, Kathleen Lourdes, B. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2018)
Shoemaking is an intangible cultural heritage of Marikina City. With the goal of documenting the shoemaking craft and arts of Marikina City through photos and interviews, the project conceptualized and created an interactive media that provided a fun and easy way to learn about shoemaking process. The interactive media was launched at the Marikina City Library and was also presented and distributed to be Marikina Shoe Industry Development Office. The researcher consulted the Marikina Shoe Industry Development Office (MASIDO), a department in the city government responsible for the footwear and leather goods industry of Marikina City, for the shoemaking process. The researcher also scheduled interviews with the oldest shoe manufacturer and shoemakers in the city.
The researcher's equipment for the project were as follows: s digital single-lens reflex camera, a mobile phone, and laptop. Minimal expenses were needed to finish the project output. The researcher limited the photo documentation of the shoemaking the process to only four shoe manufactures because they shared the same processes and problems. The researcher found out that even though some of the shoe manufacturers employed the use of machines, they still preferred the manual process; especially on the lasting operations or the shoemaking operation that sets the final shape of a shoe and holds it in place so that the outsole can be permanently attached (The Sneaker Factory, n.d.). According to Mr.Noel Box (2018), during an interviews, that the manual process was a preferred practice in Marikina because it cuts operational costs, thus making the shoes more affordable with a sizeable profit. Finally, the researcher produced an interactive media using Microsoft Power Points. The said interactive media was launched at the Marikina City Library and presented to the Marikina Shoe Industry Development Office. Researchers and students may access it offline in the library.
Special Problem (Master of Library and Information Science)
Keywords: Shoe industry -- Marikina